Implementing smartphone technology to support relational competence in foster youth: a service provider perspective. - Gomez, Efren; Alford, Keith A.; Denby, Ramona W.; Klein-Cox, Amanda (Journal of Social Work Practice, 2021)
The field of child welfare continues to search for effective ways to mitigate risks foster youth often encounter. Research discoveries about the importance of attachments and relational competence for foster youth support greater well-being. However, little is known about the use of smartphone technology and companion software in foster care as a method in promoting relational competence. This qualitative implementation study sought to explore the perceptions of child welfare providers and other stakeholders regarding how smartphone technology facilitated the ability of foster youth to become more connected with trusted adults. Research results reveal challenges associated with child welfare officials' purposeful issuance and utilisation of smartphones. Stakeholders and providers viewed these challenges as learning opportunities. Three critical themes uncovered—relationship building, youth empowerment, and normalcy—provide direction for how smartphone technology might be more efficiently tapped relative to future child welfare initiatives.